A boundary matter for a fifth-order private derivative differential equation with two double and one simple real characteristic (Eurasian Research Bulletin, 2022)
The purpose of the study is to calculate the fifth order private derivative differential equation in a more convenient way.Theoretically poorly studied, these issues are able to be widely used in many issues in mechanics.